In situ scanning tunneling microscopy (STM), atomic force microscopy (AFM) and quartz crystal microbalance (EQCM) studies of the electrochemical deposition of tantalum in two different ionic liquids with the 1-butyl-1-methylpyrrolidinium cation. (10th April 2016) - Carstens, Timo; Ispas, Adriana; Borisenko, Natalia; Atkin, Rob; Bund, Andreas; Endres, Frank
Abstract: The electrochemical reduction of 0.1 M TaF5 in two hydrophobic ionic liquids (1-butyl-1-methylpyrrolidinium tris(pentafluoroethyl) trifluorophosphate ([Py1, 4 ]FAP) and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) amide ([Py1, 4 ]TFSA) is probed using three in situ techniques: scanning tunneling microscopy (STM), atomic force microscopy (AFM), and electrochemical quartz crystal microbalance (EQCM). These techniques reveal that under similar conditions TaF5 is more easily reduced in the liquids with [TFSA] − than [FAP] − anions. Increasing the temperature reduced the viscosity and density of the ionic liquids which facilitates TaF5 electroreduction, in particular, in [Py1, 4 ]TFSA. A herringbone reconstruction of the Au electrode was observed by STM for both ionic liquids with and without TaF5 . Ta deposition was proved by STM and EQCM in [Py1, 4 ]TFSA. Cracked layers, with ionic liquid trapped inside, were obtained by direct plating from the [TFSA] − ionic liquid. No Ta containing deposits could be obtained in the liquid with the [FAP] − anion.